Accelerating Phylogeny-Aware Short DNA Read Alignment with FPGAs - Alachiotis, N; Berger, S A; Stamatakis, A (2011 IEEE 19th Annual International Symposium on Field-Programmable Custom Computing Machines, 2011)
Recent advances in molecular sequencing technology have given rise to novel algorithms for simultaneously aligning short sequence reads to reference sequence alignments and corresponding evolutionary reference trees. We present a complete hardware/software implementation for the acceleration of a program called PaPaRa, a newly introduced dynamic programming algorithm for this purpose. We verify the correctness of the proposed architecture on a real FPGA and introduce a straight-forward communication protocol(using gigabit ethernet) for seamless integration with the encapsulating steering software that is executed on a PC processor. The hardware description and the software implementation are freely available for download. When mapped to a Virtex 6 FPGA, our reconfigurable architecture can compute 133.4 billion cell updates per second for the novel, tree-based alignment kernel of PaPaRa. Compared to PaPaRa, running on a 3.2GHz Intel Core i5 CPU, we obtain speedups for the alignment kernel, that range between 170 and 471. For the entire application, that is, the alignment kernel and the trace-back step, we obtain speedups between 74 and 118.